Effects of diet type on the core fecal bacterial taxa and the dysbiosis index of healthy adult dogs - Oba, Patrícia M.; Roberts, Leah J.; Geary, Elizabeth L.; Suchodolski, Jan S.; Swanson, Kelly S. (Frontiers in Veterinary Science, 2025)
There is great interest in studying the canine gastrointestinal microbiome. In healthy dogs versus those with acute and chronic enteropathies, specific bacterial taxa have been identified that are consistently associated with shifts in the microbiome. A qPCR-based dysbiosis index (DI) that assesses microbiome shifts was developed based on a subset of these taxa. Because most dogs consume kibble diets, published data on core bacteria and the DI were largely derived from dogs consuming that diet form. Because dietary composition impacts the microbiome, it was unknown whether data from dogs consuming other diet types would adhere to reported core taxa abundance and DI guidelines. The study’s aim was to determine the fecal abundance of core bacteria and DI of dogs fed commercially available kibble vs. mildly-cooked human-grade (fresh) diets. Fecal samples collected from adult dogs across four experiments were used (4 kibble diets, n = 10–12/treatment; 4 fresh diets, n = 10–24/treatment). Moderate correlations were observed between total dietary fiber (TDF) and Fusobacterium (positive correlation), Lactobacillus (negative), and DI (negative). Dietary protein was correlated with fecal Ruminococcus gnavus (negative), while dietary fat was correlated with fecal Bacteroides and C. perfringens abundance (both positive). Dogs fed fresh diets exhibited higher (p < 0.01) abundances of Streptococcus, Escherichia coli, and Clostridium perfringens, while those fed kibble diets had higher (p < 0.05) abundances of Fusobacterium, Clostridium hiranonis, and Bacteroides. Dogs fed fresh diets had a greater (p < 0.0001) DI, but the majority of scores remained within the normal range. Dogs fed animal protein-based kibble diets had higher (p < 0.05) fecal Faecalibacterium and Fusobacterium, while dogs fed animal protein-based fresh diets had higher (p < 0.05) Streptococcus, E. coli, and C. perfringens. Bifidobacterium and Bacteroides were more abundant (p < 0.01) in dogs fed animal protein-based kibble and plant protein-based fresh diets. Dogs fed animal protein-based fresh diets had a greater (p < 0.0001) DI. Even though microbiota populations were statistically different among diets, all mean DI were <0, with only a few individual dogs consuming fresh diets having DI >0 (5 dogs >0; 1 dog >2). Overall, these data demonstrate the utility of the DI across different diet types in healthy dogs.